Oral hydrogel microspheres were used for highly specific delivery of Steamed Codonopsis lanceolata to exert the protective effects on cisplatin-induced acute kidney injury in mice. (March 2023) - Li, Yan-fei; Li, Wei; Hu, Jun-nan; Shi, Hui; Shen, Qiong; Wang, Shi-han; Jiang, Shuang; Liu, Yong-bo; Zhao, Li-chun; Wang, Zi
Graphical abstract: Highlights: Steamed Codonopsis lanceolata (SCL) has a good therapeutic effect on acute kidney injury. Sodium alginate(SA) drug - loaded microspheres have good gastric acid resistance. SCL might regulate NF-κB signaling pathways against acute kidney injury. SCL has anti-oxidant and anti-apoptotic effects. Abstract: Although Steamed Codonopsis lanceolata (SCL) has been shown to protect against acute kidney injury (AKI), Its poor stability and susceptibility to decomposition in the GI tract significantly reducing its therapeutic efficacy. Nanoscale/microscale drug delivery systems may overcome the difficulties of oral administration of phytochemicals and avoid premature drug release and degradation. In this study, we mainly loaded SCL into sodium alginate (SA) micron particles (SCL-SA), which showed significant gut-targeting and anti-gastric acid ability from in vitro and in vivo imaging fluorescence adhesion experiments. Our results showed that the levels of serum blood urea nitrogen (BUN) and creatinine (CRE) were evidently increased in cisplatin-intoxicated mice, which were reversed by SCL-SA. Renal oxidative stress, evidenced by increasing malondialdehyde (MDA) level and decrease of glutathione (GSH), catalase (CAT) and superoxide dismutase (SOD) activities, were significantly alleviated by SCL-SA pretreatment. Immunohistochemical staining showed that SCL-SA could improve cell apoptosis by decrease the expressions of BCL2-Associated X (Bax) and B-cell lymphoma-2 (Bcl-2). In addition, SCL-SA pretreatment can also inhibit the increase of serum tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) induced by cisplatin. Additionally, SCL-SA was found to reduce the expressions of nuclear factor-κB (NF-κB) signal pathways and inflammatory protein levels of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2) induced by cisplatin. Meanwhile, the contents of lobetyolin and syringin in Codonopsis lanceolata were increased after steaming. In conclusion, the reduction of AKI by SCL-SA may be due to the synergistic effect of lobetyolin and syringin. Based on the advantages of microparticles, this study provides important insights into the treatment of AKI with oral natural compounds.